Kontribusi Mutu Informasi Terhadap Efektivitas Kerja Pegawai Bidang Pendidikan Menengah dan Tinggi di Dinas Pendidikan Provinsi Jawa Barat - Azizah, Riska; Muhtaram Mirfani, Aceng; M.Pd, Suryadi (Jurnal ADPEND, 2016)
The tittle of this research is "Contribution of Information Quality of Work Effectiveness Against Employee Education and Higher Secondary Education Department of West Java Province". In general, this study aims to determine how much influence the quality of information on the effectiveness of employees working in the field Dikmenti Education Department of West Java Province. The method used in this research is descriptive method with quantitative approach. The data collection technique using a closed questionnaire distributed to 49 employees as the study population (total sampling). Weight calculation results Mean Score (WMS), shows that the quality of information included in either category with a score of 2.97 and the effectiveness of the employees included in the excellent category with a score of 3.08. Normality test results on the distribution of the data showed that the variables X and Y have normal distribution, further analysis of the data using statistical parametric. The correlation analysis using Pearson Product Moment correlation coefficient between variables X and Y is equal to 0.742 which shows that the correlation of the two variables are at the level of positive relationships and strong. Meanwhile, the results of significance test using t-test comparison is t_hitung (7.579)> t_tabel (2,012) means that there is a significant relationship between the variables X and Y. Further, test results of the coefficient of determination is that the variable X contributes to variable Y for 55% and the rest 45% influenced by other factors. Results of regression analysis equation Y = 13.955 + 0.742 X. The conclusion is evident that there is a strong and significant relationship between Quality of Work Effectiveness Against Information Officer of Secondary and Higher Education in the Education Department of West Java Province.